Factors Impacting Research Productivity of Academic Staff at the Iraqi Higher Education system - Jameel, Alaa S; Ahmad, Abd Rahman (International Business Education Journal, 2020)
Research productivity is a vital element in enhancing the university ranking and, it is an important metric to measure the performance of academic staff. The purpose of this study is to identify the factors impacting research productivity of academic staff at Cihan University Erbil, Iraq. A survey was carried out among 87 academic staff randomly selected at the university to determine the impact of Fund, Collaboration, Information and Communication Technology (ICT), and Job Satisfaction on Research Productivity. The data was analyzed by using Smart PLS 3.2.9. The results indicated that Fund, Collaboration, ICT and Job Satisfaction had positive and significant impact on Research Productivity, although Fund has the highest impact on Research Productivity. The implication of this study is the management of universities should pay greater attention on research funding opportunities, rewarding collaboration among researchers, enabling ICT and improving job satisfaction to boost research productivity of the academic staff. For future research, it is recommended to measure the mediating roles of the variables and consider sampling academic staff from other universities to increase generalizability.